Setting of import tolerance for pyraclostrobin in papayas - EFSA (European Food Safety Authority); Giulia Bellisai; Giovanni Bernasconi; Alba Brancato; Luis Carrasco Cabrera; Irene Castellan; Monica Del Aguila; Lucien Ferreira; German Giner Santonja; Luna Greco; Samira Jarrah; Renata Leuschner; et al. (EFSA Journal)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant BASF SE submitted a request to the competent national authority in Germany to set an import tolerance for the active substance pyraclostrobin in papayas imported from Brazil. The data submitted in support of the request were found to be sufficient to derive a maximum residue level (MRL) proposal for papayas. Adequate analytical methods for enforcement are available to control the residues of pyraclostrobin on the commodity under consideration at or above the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of pyraclostrobin on papayas imported from Brazil according to the reported agricultural practices is unlikely to present a risk to consumer health.